Microhabitat and stopover site selection by juvenile Western Rattlesnakes (Crotalus oreganus) - Howarth, Chloe R.; Bishop, Christine A.; Larsen, Karl W. (Frontiers in Amphibian and Reptile Science, 2023)
Studies on habitat selection are central to our understanding of animal ecology and play an important role in the conservation and management of species. However, habitat selection is not necessarily consistent across sectors of populations and failing to understand both similarities and differences between age classes, for instance, may be problematic. Knowledge on habitat use by juvenile vertebrates in general is sorely lacking, particularly for species with precocial offspring, and here we address this gap by describing habitat use by juvenile Western Rattlesnakes (Crotalus oreganus). We measured habitat at two scales for radio-telemetered juvenile snakes along active-season movement paths at a site in southern British Columbia, Canada, where seasonal migrations and habitat associations of adult animals have been particularly well studied. Despite the relatively short distances these animals travelled and their diminutive size, we found there was selection for structurally stable cover (e.g., woody debris, shrub, and rock cover) similar to that documented for adult snakes in the same region. Additionally, we tested for differences in microhabitat features at sites used for short-duration (fewer than seven days) and long-duration (seven days or longer) stopovers: we detected negative selection for leaf litter at long-duration stopover sites, but otherwise identified no difference in the microhabitat features associated with these two categories of locations. Overall, this study contributes rare data to our growing understanding of the complexity of habitat requirements for migratory snake species, including northern crotalid vipers, while underscoring the crucial role of habitat selection research across all segments of populations. Comparative data on habitat selection by early-age classes within reptile populations informs conservation planning for the long-term survival of wild populations.